Strengthening capacity of national government to develop bankable project pipelines for mobilizing climate finance: Training outcomes from the state department for the ASALs and regional development - Jalango, Dorcas; Binge, Brenda; Gamoyo, Majambo; Chilambe, Pedro; Denje, Telvin; Ogaba, Angela; Njasi, Abigail (2025)
Kenya’s Arid and Semi-Arid Lands (ASALs), covering nearly 80% of the country, are experiencing intensifying climate impacts that threaten pastoralist and smallholder livelihoods reliant on rainfall. Recurrent droughts and floods, alongside ecosystem degradation, are driving food and water insecurity, resource-based conflict, and heightened economic vulnerability. The State Department for the ASALs and Regional Development is central to advancing climate-resilient development in these regions through institutional strengthening, investment planning, and preparation of bankable project proposals to mobilize climate finance for transformative interventions, while also building strategic partnerships. However, limited technical capacity and constrained financial resources continue to hinder effective project design and implementation. To address these gaps, the Alliance of Bioversity International and CIAT, together with the African Group of Negotiators Expert Support (AGNES), convened a training and working session for national and county ASAL representatives. The workshop aimed to build skills for developing high-quality, investment-ready climate adaptation proposals and to create a pipeline of viable projects for engagement with development partners and funding institutions. Expected outcomes included a portfolio of draft proposals aligned with national and county priorities, stronger competencies in climate rationale, theory of change, logical framework development, and budget alignment, and improved coordination among national and regional actors to mobilize climate finance.